Thermodynamical and self-consistent approach to inelastic ferromagnetic polycrystals - Mićunović, M. (Archives of Mechanics, 2006)
Geometric and kinematic aspects of intragranular as well as intergranular plastic deformation of ferromagnetic polycrystals are discussed. Elastic strain is covered by the effective field homogenization method inside a representative volume element (RVE). By applying this method, an effective magnetostriction 4-tensor is determined. The evolution equation formed by tensor representation having incremental form is postulated to model inelastic metals. The rate-dependence takes place by means of stress rate-dependent value of the initial yield stress. Concept of the M. Zorawski deformation geometry is extended on the basis of constrained micro- and free macrorotations in intermediate reference configuration. This has as a consequence that the evolution equation for plastic spin of RVE is an outcome of the evolution equation for plastic stretching. The macroscopic evolution equation is based on Vakulenko’s concept of thermodynamic time. A tensor representation for magnetomechanical interaction is proposed and susceptibility coefficients for iron are calibrated.